Application of MCDM based hybrid optimization of WEDM process parameters. (2022) - Sreeraj, P.; Thirumalai Kumaran, S.; Suresh Kumar, S.; Uthayakumar, M.; Pethuraj, M.
Abstract: This work investigates the process parameters like peak current, applied voltage, wire feed rate on machining characteristics kerf width and surface roughness of Wire Electrical Discharge Machine (WEDM) while machining AA6351/Rutile composite which is fabricated by powder metallurgy technique. In this experimental work, Taguchi's L27 orthogonal design is used for conducting experiments. This present research has been intended to optimize the setting of process parameters in order to improve the machining performance by coupling different Multi-Criterion Decision making methods such as Multi-Objective Optimization process on the basis of Ratio Analysis (MOORA) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) with Principal Component Analysis (PCA). When the hybrid MOORA-PCA and TOPSIS-PCA are applied, the results display with a peak current 12 amps, applied voltage 20 V and wire feed rate 5 m/min. When compared these two hybrid methods, MOORA-PCA approach clearly indicates its significance because of its simplicity. The optimised setting obtained canbe further used to produce high quality micro-channels for heat exchangers and heat sinks.